A Cross-Sectional Comparison of Drinking Patterns, Alcohol Use and Related Medical Morbidities in a Secondary Versus Tertiary Setting - Risal, A; Tharoor, H (Kathmandu University Medical Journal, 2015)
Background Alcohol Dependence exists in different spectrums at different settings and associated with various medical morbidities, disability and health care utilization costs. Objectives To study the drinking patterns, alcohol use disorders and alcohol related medical morbidities in patients diagnosed with Alcohol Dependence Syndrome (ADS) and attending out / in-patient psychiatry services at secondary and tertiary care centre. Methods A cross-sectional comparative study was done among the patients diagnosed with ADS attending psychiatry services at District hospital, Udupi and Kasturba Hospital, Manipal. Serial sampling was done. Patients having any other psychiatric illnesses were excluded. The two groups were compared in relation to socio-demographic variables, drinking related variables, patterns of drinking and alcohol related medical morbidities identified. Results Significant differences in some socio-demographic parameters among the patients from the two different treatment centers were found with secondary level hospital (N=50) having more illiterate, laborers and below the poverty line population in comparison to the tertiary level hospital (N=75). Maximum frequency of gastro-intestinal morbidities was seen in both the hospital population, irrespective of the patterns of drinking. Conclusion Alcohol use disorders and alcohol related medical morbidities show some variations in their presentations in the different treatment centers. DOI: http://dx.doi.org/10.3126/kumj.v11i2.12492 Kathmandu University Medical Journal Vol.11(2) 2013: 152-157